Phonon stability and phonon transport of graphene-like borophene. (19th May 2020) - Yin, Yan; Li, Dengfeng; Hu, Yanxiao; Ding, Guangqian; Zhou, Hangbo; Zhang, Gang
Abstract: Recent decades have seen tremendous progress in quantitative understanding of phonon transport, which is critical for the thermal management of various functional devices and the proper optimization of thermoelectric materials. In this work, using a first-principles based calculation combined with the non-equilibrium Green's function and a phonon Boltzmann transport equation, we provide a systematic study of the phonon stability and phonon transport of a monolayer boron sheet with a honeycomb, graphene-like structure (graphene-like borophene) in both ballistic and diffusive regimes. For free-standing graphene-like borophene, phonon instabilities occur near the centre of the Brillouin zone, implying elastic instability. Investigation of the electronic structures shows that the phonon instability is due to the deficiency of electrons. Our first-principles results show that with net charge doping and in-plane tensile strain, graphene-like borophene becomes thermodynamically stable in ideal planar nature, because the bonding characteristic is modified. At room temperature, the ballistic thermal conductance of graphene-like borophene (7.14 nWK −1 nm −2 ) is higher than that of graphene (4.1 nWK −1 nm −2 ), due to high phonon transmission. However, its diffusive thermal conductivity is two orders of magnitude lower than graphene, because the phonon relaxation time is dramatically reduced compared with its carbon counterpart. Although the phonon group velocity and phonon anharmonicity are comparable with those of graphene, the suppressed phonon space results in dramatically strong phonon–phonon scattering. These thermal transport characteristics in both ballistic and diffusive regimes are of fundamental and technological relevance and provide guidance for applications of boron-based nanomaterials in which thermal conduction is the major concern.